SELF-DIRECTED LEARNING METHOD (SDL) TO ENHANCE SPEAKING SKILL - Syamsuriani, Syamsuriani; Rossydi, Ahmad; Octavianie, Adhitya; Rochmawati, Laila (University of Muhammadiyah Malang, 2024)
The efficacy of self-regulated learning in the context of language acquisition has been widely acknowledged. This study demonstrates the impact of self-regulated learning on the enhancement of students' speaking abilities. Within the context of English as a Foreign Language (EFL), the act of speaking is commonly regarded as a formidable undertaking that necessitates the utilization of various actions, skills, and strategies to attain effective communication. Digital portfolios have a significant impact on language learning as they encompass learners' actions, skills, and strategies in classroom planning. This research investigated the influence of self-regulation processes on students' performance in speaking tasks in English as a Foreign Language (EFL) classes at Politeknik Penerbangan Jayapura. The primary outcomes that were observed encompassed the phases of anticipation, realization, and reflection in speaking tasks. The findings of the study indicate that individuals who possess self-regulatory skills can effectively communicate when they possess a comprehensive understanding of the task at hand and can regulate their actions accordingly.